(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2003)
A man was found hanged by a tree. Police transported him to mortuary in the evening of 02.11.2002 and on the same day due to mass casualty nine other bodies were brought to mortuary at different intervals of time. Postmortem of body with alleged hanging was conducted on 03.11.2002 & it was found that his right hand below wrist & toes of right foot except part of great toe were missing. But these injuries were not mentioned in inquest submitted by police. The police officer was called, who stated that these injuries were not present at the time of preparation of inquest at the scene of crime & he was having photograph of scene of crime to prove it also.